A genome-wide association study implicates the BMP7 locus as a risk factor for nonsyndromic metopic craniosynostosis - Justice, CM; Cuellar, A; Bala, K; Sabourin, JA; Cunningham, ML; Crawford, K; Phipps, JM; Zhou, Y; Cilliers, D; Byren, JC; Johnson, D; Wall, SA; et al. (Springer Nature, 2020)
Our previous genome-wide association study (GWAS) for sagittal nonsyndromic craniosynostosis (sNCS) provided important insights into the genetics of midline CS. In this study, we performed a GWAS for a second midline NCS, metopic NCS (mNCS), using 215 non-Hispanic white case-parent triads. We identified six variants with genome-wide significance (P ≤ 5 × 10–8): rs781716 (P = 4.71 × 10–9; odds ratio [OR] = 2.44) intronic to SPRY3; rs6127972 (P = 4.41 × 10–8; OR = 2.17) intronic to BMP7; rs62590971 (P = 6.22 × 10–9; OR = 0.34), located ~ 155 kb upstream from TGIF2LX; and rs2522623, rs2573826, and rs2754857, all intronic to PCDH11X (P = 1.76 × 10–8, OR = 0.45; P = 3.31 × 10–8, OR = 0.45; P = 1.09 × 10–8, OR = 0.44, respectively). We performed a replication study of these variants using an independent non-Hispanic white sample of 194 unrelated mNCS cases and 333 unaffected controls; only the association for rs6127972 (P = 0.004, OR = 1.45; meta-analysis P = 1.27 × 10–8, OR = 1.74) was replicated. Our meta-analysis examining single nucleotide polymorphisms common to both our mNCS and sNCS studies showed the strongest association for rs6127972 (P = 1.16 × 10–6). Our imputation analysis identified a linkage disequilibrium block encompassing rs6127972, which contained an enhancer overlapping a CTCF transcription factor binding site (chr20:55,798,821–55,798,917) that was significantly hypomethylated in mesenchymal stem cells derived from fused metopic compared to open sutures from the same probands. This study provides additional insights into genetic factors in midline CS.